Isolated Gallbladder Perforation in Cases of Blunt Trauma Abdomen - Gupta, MK; Ahmad, K; Kumar, A; Santhalia, PK; Joshi, BR; Rauniyar, RK (Nepalese Journal of Radiology, 2014)
Isolated perforation of gallbladder (GB) following blunt trauma abdomen is extremely rare and may pose a diagnostic challenge. Early diagnosis and treatment is of paramount importance to reduce morbidity and mortality associated with GB perforation. We present two cases of isolated GB perforation in patients of blunt abdominal trauma diagnosed on multi-detector computed tomography (MDCT) which was corroborated by bile stained peritoneal aspirate and subsequently confirmed by surgery. Both the patients underwent open cholecystectomy with good outcome. DOI: http://dx.doi.org/10.3126/njr.v3i2.9614 Nepalese Journal of Radiology Vol.3(2)July-Dec, 2013: 72-76